Allometry of factor VIII and informed scaling of next‐generation therapeutic proteins. Issue 7 (25th April 2013) - Kosloski, Matthew P.; Pisal, Dipak S.; Mager, Donald E.; Balu‐Iyer, Sathy V.
Abstract Allometric scaling has been applied to the pharmacokinetics (PK) of factor VIII (FVIII), but published relationships are based on relatively small subsets of available data. Numerous next‐generation forms of FVIII are being developed (e.g., Fc fusion, PEGylated, and liposomal formulations) and traditional PK scaling of these products would not incorporate the wealth of existing knowledge for current FVIII therapy in humans. We conducted a meta‐analysis and developed allometric relationships of FVIII from over 100 PK studies collected from literature. Normalized Wajima curves were used to relate mean FVIII profiles between species. An "informed scaling" approach was derived for predicting first‐in‐human PK parameters and demonstrated with a case study for an Fc fusion FVIII. NCA values for FVIII PK were well described by the allometric equations CL = 6.59 W0.85 and Vss = 65.0 W0.97. A subset of studies characterized by two‐compartment modeling showed strong linearity in scaling of total clearance (CL) and central volume, but more variability in distributional CL and peripheral volume. Wajima curves for FVIII superimposed across species and the disposition of Fc fusion FVIII in humans was well predicted by "informed scaling." This approach might be generally applicable for predicting human PK of next‐generational therapeutics. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2380–2394, 2013